Childhood onset inflammatory bowel disease and risk of cancer: a Swedish nationwide cohort study 1964-2014. (20th September 2017) - Olén, O; Askling, J; Sachs, MC; Frumento, P; Neovius, M; Smedby, KE; Ekbom, A; Malmborg, P; Ludvigsson, JF
Abstract : Objective To assess risk of cancer in patients with childhood onset inflammatory bowel disease in childhood and adulthood. Design Cohort study with matched general population reference individuals using multivariable Cox regression to estimate hazard ratios. Setting Swedish national patient register (both inpatient and non-primary outpatient care) 1964-2014. Participants Incident cases of childhood onset (<18 years) inflammatory bowel disease (n=9405: ulcerative colitis, n=4648; Crohn's disease, n=3768; unclassified, n=989) compared with 92 870 comparators from the general population matched for sex, age, birth year, and county. Main outcome measures Any cancer and cancer types according to the Swedish Cancer Register. Results During follow-up through adulthood (median age at end of follow-up 27 years), 497 (3.3 per 1000 person years) people with childhood onset inflammatory bowel disease had first cancers, compared with 2256 (1.5 per 1000 person years) in the general population comparators (hazard ratio 2.2, 95% confidence interval 2.0 to 2.5). Hazard ratios for any cancer were 2.6 in ulcerative colitis (2.3 to 3.0) and 1.7 in Crohn's disease (1.5 to 2.1). Patients also had an increased risk of cancer before their 18th birthday (2.7, 1.6 to 4.4; 20 cancers in 9405 patients, 0.6 per1000 person years). Gastrointestinal cancers had the highest relative risks, with a hazard ratio of 18.0 (14.4 to 22.7) corresponding to 202 cancers in patients with inflammatory bowel disease. The increased risk of cancer (before 25th birthday) was similar over time (1964-1989: 1.6, 1.0 to 2.4; 1990-2001: 2.3, 1.5 to 3.3); 2002-06: 2.9, 1.9 to 4.2; 2007-14: 2.2, 1.1 to 4.2). Conclusion Childhood onset inflammatory bowel disease is associated with an increased risk of any cancer, especially gastrointestinal cancers, both in childhood and later in life. The higher risk of cancer has not fallen over time.